Experimental study on preventing expanded polystyrene concrete segregation. Issue 10 (8th June 2018) - You, Quan; Miao, Linchang; Li, Chao; Hu, Shengkun; Fang, Huanglei
Abstract : The hydrophobicity of expanded polystyrene beads means that unexpected segregation of expanded polystyrene concretes can occur. In order to determine the segregation of expanded polystyrene concretes, a class of tests was conducted, and relevant indices including strength, fluidity and the extent of segregation were measured. Compressive strengths in different directions and different volume fractions were employed to define the strength anisotropy index and the segregation index, respectively. The fluidity test results indicated that the miniature slump cone test could be performed as a substitute for the standard slump cone for practical and economic reasons. The fluidity had larger impact on the strength of expanded polystyrene concretes compared with plain concretes. In addition, an approximately linear correlation was found between the segregation and the strength anisotropy index. By comprehensive inspection of the fluidity, strength and extent of segregation of expanded polystyrene concretes, the most reasonable mixture proportion was found. By considering segregation inhibition in the design of mixture proportions, the proposed experimental method can be used in engineering practice relating to expanded polystyrene concretes.